Three-Dimensional Imaging of Lower Limb Neuropathies - Ahlawat, Shivani; Carrino, John A. (Seminars in Musculoskeletal Radiology, 2015)
Peripheral nerve pathology can be detected on high-resolution MRI on the basis of primary or secondary findings. Primary findings of nerve pathology include alterations in signal, course, and caliber; secondary findings include skeletal muscle denervation. Although two-dimensional (2D) MRI sequences comprised of a combination of fluid-sensitive and non–fat-suppressed anatomical sequences can detect changes in nerve size, signal, course, and architecture, three-dimensional (3D) imaging can play an important role in the detection and characterization of nerve pathology including caliber changes at typical compression sites, anomalous course, and nerve discontinuity. This article discusses the benefits of 3D MRI with respect to lower limb neuropathies. The article also reviews the normal anatomy of the nerves in the lower extremity from the hip joint to the foot, and it illustrates common causes and the imaging appearance of lower limb peripheral neuropathy.
Keywords: 3D MRI; lower limb neuropathy; entrapment